The effects of acute and chronic Red Bull® consumption on cardiodynamics and oxidative stress in coronary effluent of trained rats - Pušica, Irena; Đorđević, Dušica; Bradić, Jovana; Jeremić, Jovana; Srejović, Ivan; Živković, Vladimir; Jakovljević, Vladimir (Vojnosanitetski pregled, 2021)
Background/Aim. Energy drinks (EDs) are widely used by athletes as ergogenic agents and Red Bull® is one of the most consumed EDs among them. The aim of this study was to determine the acute and chronic effects of Red Bull® on cardiodynamics and parameters of oxidative stress in physically trained rats. Methods. Rats were subjected to a swimming practice (1h a day, 5 days a week, for 4 weeks). They were divided into 4 groups: rats that did not consume ED either before swimming or prior to sacrificing; rats that did not consume ED before swimming but did consume ED 30 min prior to sacrificing; rats that consumed ED 30 min before every swimming training but did not consume ED prior to sacrificing; rats that consumed ED 30 min before every swimming training and 30 min before sacrificing. After sacrificing, the hearts of the rats were isolated and perfused according to the Langendorff technique. The parameters of cardiac function were recorded, and also the levels of prooxidants were measured in the coronary effluent during coronary autoregulation. Results. Acute administration of the ED had a positive inotropic effect (manifested as a significantly higher level of the maximum and minimum rate of pressure development in the left ventricle), while chronic administration affected the isolated increase in systolic left ventricular pressure. The prooxidative effect of the ED was observed, which was more pronounced in chronic consumption. Conclusion. The main conclusion of our study is that chronic consumption of ED changes the cardiovascular response and redox status in acute consumption ED.